ANALYSIS THE EFFECTS OF INJECTION STRATEGIES ON COMBUSTION CHARACTERISTICS AND POLLUTANT EMISSIONS IN A MULTIPLE DIRECT INJECTION DIESEL ENGINE - Firat, Mujdat; Varol, Yasin (Turkish Soc Thermal Sciences Technology, 2019)
An advanced CFD simulation has been performed to explore different spray cone angles and multiple-fuel injection on combustion characteristics and emission formations in a DI-diesel engine. The in-cylinder pressure, temperature, heat release rate, combustion progresses and formation of emissions are simulated at different spray cone angles with AVL-FIRE code. An improved version of the ECFM-3Z combustion model has been applied and coupled with advanced Zeldovich and Kinetic models for NO and soot formation, respectively. After the validation of cylinder pressure and heat release rate experimental engine tests, further numerical simulations were performed to investigate the effects of spray cone angles. It has been determined that the cylinder peak pressure and heat release rate were slightly increased by 120 degrees and 160 degrees spray cone angles. The NO mass fraction is the lowest at a spray angle of 150 degrees, while the soot mass fraction is the lowest at spray cone angles of 120 degrees and 160 degrees. Simulations of all configurations were subsequently performed to understand the effects of in-cylinder parameters during the combustion stroke. These results are significant enough to affect the combustion process and completely change the next generation of emissions.
Keywords: Multiple injections; Diesel combustion; Pollutant emissions; CFD simulation